1996
DOI: 10.1136/hrt.75.6.596
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow up of patients with dilated heart muscle disease treated with human leucocytic interferon alpha or thymic hormones initial results.

Abstract: (Heart 1996;75:596-601)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…Interferon-␣ benefit was described in a case study 117 and in a single-center, randomized trial comparing its efficacy to placebo or thymomodulin. 118 Although mortality did not differ, LVEF rose significantly more in the treatment than the placebo group. Interferon-␤ has also been shown to produce benefit in a phase II, single-center study of patients with PCR-detected enteroviral or adenoviral genome on endomyocardial biopsy.…”
Section: Treatmentmentioning
confidence: 95%
“…Interferon-␣ benefit was described in a case study 117 and in a single-center, randomized trial comparing its efficacy to placebo or thymomodulin. 118 Although mortality did not differ, LVEF rose significantly more in the treatment than the placebo group. Interferon-␤ has also been shown to produce benefit in a phase II, single-center study of patients with PCR-detected enteroviral or adenoviral genome on endomyocardial biopsy.…”
Section: Treatmentmentioning
confidence: 95%
“…On the basis of the results from both virus-and CM-induced models of myocarditis, IFN-␥ may be an appropriate candidate. Miric et al 30 showed the efficacy of IFN-␣ treatment in patients with biopsy-proven myocarditis and dilated cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…It can be fatal in infants and, although usually resolved in adults, can progress to chronic myocarditis and/or dilated cardiomyopathy with concomitant cardiac failure (11,28). Recent clinical studies have indicated that alpha interferon (IFN-␣) (11,21,35,36) and IFN-␤ (29) can reduce the severity of viral myocarditis, inhibiting viral replication and improving cardiac function. Nonetheless, viral myocarditis remains a disease without reliable treatment, and the prognosis remains poor for more than half of patients presenting with clinical symptoms (45).…”
mentioning
confidence: 99%